Refleksi Tata Kelola Perairan Tradisional Handil dan Saka dalam Drainase Perumahan Kota di Banjarmasin - Wasita Wasita; Sunarningsih Sunarningsih (Badan Riset dan Inovasi Nasional (BRIN), 2022)
The tradition of Banjar farmers in making artificial rivers for water management in rice fields can be adopted as city drainage, especially in housing complexes. For the adoption to be successful, it is necessary to pay attention to how the water flow works to ensure its implementation, as well as development. The method used in this paper is qualitative. Data were collected based on direct observation activities, and supplemented with secondary data in the form of written sources, documents, pictures, and maps. The analysis was carried out by descriptive, comparison, and interpretation. The result obtained is the natural flow of water in artificial rivers applying a gravity system which is realized by placing attention to heights, in order from highest to lowest, rice fields, saka, handil, and natural rivers. The adoption of this pattern for drainage in housing complexes needs to take into account of the basic concept, and be developed according to current conditions. Therefore, it can be concluded that the way of regulation works with artificial river facilities is feasible to be adopted and applied to drainage in the current housing complexes.